Measurements of the tt¯ production cross section in lepton+jets final states in pp collisions at 8 TeV and ratio of 8 to 7 TeV cross sections - Khachatryan, Vardan; Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Asilar, Ece; Md. Ali, Mohd. Adli (Springer New York, 2017)
A measurement of the top quark pair production (tt) cross section in proton–proton collisions at the centre-of-mass energy of 8 TeV is presented using data collected with the CMS detector at the LHC, corresponding to an integrated luminosity of 19.6 fb−1. This analysis is performed in the tt decay channels with one isolated, high transverse momentum electron or muon and at least four jets, at least one of which is required to be identified as originating from hadronization of a b quark. The calibration of the jet energy scale and the efficiency of b jet identification are determined from data. The measured tt cross section is 228.5 ± 3.8 (stat) ± 13.7 (syst) ± 6.0 (lumi) pb. This measurement is compared with an analysis of 7 TeV data, corresponding to an integrated luminosity of 5.0 fb−1, to determine the ratio of 8 TeV to 7 TeV cross sections, which is found to be 1.43 ± 0.04 (stat) ± 0.07 (syst) ± 0.05 (lumi). The measurements are in agreement with QCD predictions up to next-to-next-to-leading order.